Analysis of soluble thrombomodulin contents in blood serum of patients with non-valvular atrial fibrillation: gender dependence - O. N. Ogurkova; T. E. Suslova; Yu. G. Lugacheva; M. A. Dragunova; E. S. Sitkova; R. E. Batalov (Медицинская иммунология)
Recent studies have demonstrated increased interest in development of new laboratory methods for assessing the risk of thromboembolic complications in atrial fibrillation. Soluble thrombomodulin (sTM) is one of the biomarkers that exhibit important anti-inflammatory, anticoagulant and antifibrinolytic properties and are involved in maintenance of vascular homeostasis. Our objective was to study the contents of soluble thrombomodulin (sTM) in blood serum of the patients with non-valvular atrial fibrillation receiving anticoagulant therapy with a history of thrombotic complications versus a group of patients with atrial fibrillation without thrombotic complications. The study included 60 patients over 18 years of age diagnosed with atrial fibrillation, which was verified according to clinical recommendations, who received anticoagulant therapy. Of this group, 21 patients developed thrombotic complications during adequate anticoagulant therapy. 22 healthy volunteers were also included into the study. Evaluation of soluble thrombomodulin in blood serum was carried out by ELISA technique using the facilities at the Center for Collective Use “Medical Genomics” of the Tomsk National Research Medical Center. All the examined patients were divided into 2 groups: a group of patients with atrial fibrillation without thrombotic complications (TC), and a group of patients with atrial fibrillation who developed TC. The sTM content in blood serum of patients with thrombotic complications was reduced, when compared with results obtained in patients without thrombotic complications, and among healthy volunteers. Analysis of the sTM level in men and women in groups of patients and in healthy volunteers showed that the values of this serum biomarker were lower in female patients with atrial fibrillation and TC, when compared with women from the group of patients without TC and with healthy females. Moreover, the content of soluble thrombomodulin prove to be reduced in men with thrombosis compared to healthy males. A comparative analysis of sTM levels in women and men in all groups did not reveal statistically significant differences. In the studied group of patients with non-valvular atrial fibrillation receiving anticoagulant therapy, a decrease in sTM levels was noted in the subgroup of patients with TC.